2020
DOI: 10.3389/fchem.2020.00581
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Macrophage Immunomodulatory Activity Induced by a New Polysaccharide Isolated From Polyporus umbellatus (Pers.) Fries

Abstract: Bladder cancer is one of the most malignant tumors closely associated with macrophage immune dysfunction. The Chinese medicine polyporus has shown excellent efficacy in treating bladder cancer, with minimal side effects. However, its material basis and mechanism of action remain unclear. A new water-soluble polysaccharide (HPP) with strong immunomodulatory activity was isolated from the fungus Polyporus umbellatus (Pers.) Fries. HPP had an average molecular weight of 6.88 kDa and was composed mainly of an <-(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…28 The induction of TLR expressions is one of the molecular mechanisms for the polysaccharides' immune-enhancing effect. 29 Therefore, we aimed to ascertain the regulatory effect of PSPP-1 on the expressions of TLR2 and TLR4 on RAW264.7 cells by western blot. RAW264.7 is a mouse macrophage cell line with abundant expression of TLR on the cell membrane and is a good model for the study of the TLR-mediated signaling pathway.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The induction of TLR expressions is one of the molecular mechanisms for the polysaccharides' immune-enhancing effect. 29 Therefore, we aimed to ascertain the regulatory effect of PSPP-1 on the expressions of TLR2 and TLR4 on RAW264.7 cells by western blot. RAW264.7 is a mouse macrophage cell line with abundant expression of TLR on the cell membrane and is a good model for the study of the TLR-mediated signaling pathway.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…PRRs have been reported to participate in signal transmission of macrophages, and TLRs play a key role in innate immune responses to enhance the defense system . The induction of TLR expressions is one of the molecular mechanisms for the polysaccharides’ immune-enhancing effect . Therefore, we aimed to ascertain the regulatory effect of PSPP-1 on the expressions of TLR2 and TLR4 on RAW264.7 cells by western blot.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, whether HPP promotes the polarization of TAMs toward the M1 phenotype trough NF-κB remains unclear. Activated macrophages can secrete NO, which plays an important role in antitumor cells and microorganisms ( 20 , 32 ). Here, we demonstrated that HPP dose-dependently upregulated the secretion of pro-inflammatory factors such as IL-6, TNF-α, NO, MIP-1α and MIP-1β as well as NO in macrophages trough NF-κB in TME.…”
Section: Discussionmentioning
confidence: 99%
“…The new polysaccharide was first isolated from polyporus total polysaccharide using Sephadex G-100 gel-filtration column (2.9 × 50cm), which was proven to have an α-(1→ 4)-linked D-galactan backbone ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…The bands at 1,147, 1,076, and 1,030 cm −1 were attributed to the stretching vibration of pyran ring (Dong et al, 2016). In addition, the bands at 874 cm −1 were β-glycosidic bands, and the bands at 805 cm −1 were α-glycosidic bands (Azmi et al, 2012;Liu et al, 2020), indicating that PPp-W contained an αand β-pyranose ring.…”
Section: Ft-ir Analysismentioning
confidence: 96%